Deterministic load balancing in computer networks - Xiaotie Deng; Hai-Ning Liu; Bing Xiao (Parallel and Distributed Processing, 2nd IEEE Symposium On, 1990)
The paper presents theoretical analysis of the deterministic complexity of the load balancing problem (LBP). Because of difficulty of the general problem, research in the area mostly restricts itself to probabilistic or approximation algorithms, or to the average behavior of a network. The paper provides deterministic analysis of the problem for general networks. It focuses on the worst-case complexity analysis of the problem. It shows certain cases of the LBP to be NP-complete. The paper also discusses situations closely related to computer networks, where there is a global view of load distribution in the network; it provides a polynomial algorithm for solving the load balancing problem in this network.< >